The Effectiveness of SQ4R Model on Reading Comprehension Skill Of Grade 5th Elementary Students - Kholida, Farah Diana; Rini, Titis Angga; Muzaki, Ferril Irham (Proceedings Series of Educational Studies, 2024)
The ability to read comprehension is very important where the more skillful a person is inunderstanding a reading, the easier it is for him to receive the information contained and the meaningin a reading. The reality of reading comprehension problems in Indonesia shows that the reading skills of elementary school students are low. As a form of improving the quality of students in readingcomprehension, it is necessary to have special treatment to further hone students' skills. Efforts thatcan be made include providing the right learning model. One of the learning models that is consideredto improve students' reading comprehension skills is the SQ4R (Survey, Question, Read, Recite,Review, Reflect) learning model. This study aims to examine the effectiveness of using the SQ4Rlearning model in improving students' reading comprehension skills. The type of research used ispre-experiment using one-group pretest posttest design. The results showed that the use of the SQ4Rlearning model was considered effective in improving reading comprehension skills by obtaining asignificance of 0.001